2015
DOI: 10.1038/srep14203
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous CLEAs-silica composite microparticles with high activity and enhanced stability

Abstract: A novel enzyme immobilization approach was used to generate mesoporous enzymes-silica composite microparticles by co-entrapping gelatinized starch and cross-linked phenylalanine ammonia lyase (PAL) aggregates (CLEAs) containing gelatinized starch into biomemitic silica and subsequently removing the starch by α-amylase treatment. During the preparation process, the gelatinzed starch served as a pore-forming agent to create pores in CLEAs and biomimetic silica. The resulting mesoporous CLEAs-silica composite mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…As a result, they have attracted great interest as matrix materials for enzyme immobilization. [11][12][13][14][15][16][17][18][19][20][21][22][23] Various studies have shown that MCM-41 materials have a pore size of just 3.0 nm, and are thus limited to the immobilization of enzymes with small sizes. [15][16][17] Furthermore, despite their high surface areas (ca.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they have attracted great interest as matrix materials for enzyme immobilization. [11][12][13][14][15][16][17][18][19][20][21][22][23] Various studies have shown that MCM-41 materials have a pore size of just 3.0 nm, and are thus limited to the immobilization of enzymes with small sizes. [15][16][17] Furthermore, despite their high surface areas (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Wu and co-workers demonstrated that CLEAs of lipase in alginate beads has higher stability and the leaching of immobilized lipase was prevented [12]. Cui et al reported entrapment of CLEAs of phenylalanine ammonia lyase in mesoporous silica microparticles without leaching over 10 days [22]. Haider and Husain also reported the immobilization of ␤-galactosidase in alginate beads, and the leaching of ␤-galactosidase from the alginate beads was successfully prevented [23].…”
Section: Introductionmentioning
confidence: 94%
“…In some cases, enzymes in CLEAs even showed higher activities and better stability than free enzymes [18]. Because the size of CLEAs prepared in batch processes often falls in the range of 1-10 m [19], immobilized CLEAs in alignate beads did not experience leaching problems [12,14,[20][21][22][23][24]. For example, Xu and Yang reported the encapsulation of cross-linked tyrosinase aggregates in alginate beads.…”
Section: Introductionmentioning
confidence: 97%
“…A very broad variety of materials can be used as supports for enzyme immobilization [27]. These materials may be divided into organic [28], inorganic [29] and hybrid [30] or composite [31].…”
Section: Introductionmentioning
confidence: 99%